REVIEW SENYAWA BIOAKTIF DAN KONSTITUEN KIMIA DARI TANAMAN COLEUS SEBAGAI KANDIDAT OBAT (REVIEW OF BIOACTIVE COMPOUNDS AND CHEMICAL CONSTITUENTS FROM COLEUS PLANTS AS DRUG CANDIDATES) - Dian Natasya; Marsella Oktavioni; Yusnaidar Yusnaidar; Indra Lasmana Tarigan (Tanjungpura University, 2023)
Miana plants (Coleus) are plants with compound interest types. Miana leaves have various bioactive compounds and are widely used to treat various diseases such as fever, colds, coughs, headaches, asthma, constipation, and skin diseases. There are several types of miana plants, such as Coleus scutellarioides (L.) Benth., Coleus aromaticus Benth., Coleus atropurpureus (L.) Benth. and Coleus blumei benth. This review aims to review the content of bioactive compounds and chemical constituents of the plant and its potential as a drug candidate. The method applied to the review articles is in the form of literature studies from national and international journals. Based on the data used, the n-hexane extract of miana leaves found 11 chemical compounds. Then based on the phytochemical screening of miana plants, several bioactive compounds were produced such as sterols, terpenoids, alkaloids, phenols, flavonoids, amino acids, glycosides, lactones, catechols, and tannins. The function of the Coleus aromaticus plant is as an antioxidant, antiepileptic, antiurolytic, anticancer, antidiabetic, anthelmintic, antiviral, antiprotozoal activity, the inhibitory activity of microorganisms, against digestive diseases, respiratory disorders, and against cardiovascular disorders